LMI-SI and Scharioth Additional Intraocular Lenses for Age-Related Macular Degeneration. Review - M. M. Bikbov; O. I. Orenburkina (Oftalʹmologiâ, 2019)
Currently, the treatment of neovascular age-related macular degeneration (AMD) includes: intravitreal injections (bevacizumab, ranibizumab, aflibercept, pegaptanib, etc.), photodynamic therapy, surgical treatment (subretinal surgery, recombinant tissue plasminogen activator + gas, macula translocation) and etc. Rehabilitation of these patients is carried out using special optical tools (glasses, magnifying lenses, loupes, electronic devices). Classic external devices for the correction of very poor eyesight are not convenient to use: they are often lost or forgotten at home, not adapted for constant wear, people are embarrassed to use them in public places. This review presents the characteristics and clinical results of the implantation of two intraocular lenses, the Lipschitz Macular Implant (LMI-SI) and the Scharioth Macula lenses, in patients with age-related macular degeneration (AMD). These IOL can be implanted during standard phacoemulsification with the implantation of usual posterior chamber IOL or years after the cataract extraction, which makes them unique among other lenses that are implanted only during the cataract extraction procedure. The Lipschitz Macular Implant (Israel, 2013) is a rigid IOL made of polymethyl methacrylate (PMMA), implanted in a capsular bag, it requires an incision up to 6 mm. A positive feature of the Scharioth Macula lens (1stQ GmbH, Germany, 2017) is the smallest incision needed for implantation — no more than 3 mm. This lens consists of a biocompatible hydrophilic acryl with a UV filter, the peripheral zone of the lens is optically neutral, the square design excludes its free rotation. Also, this lens can be used as therapy for progressive macular dystrophy of various etiologies. The additional macular IOLs do not affect peripheral vision, reduce binocularity when reading, and require complex visual rehabilitation.